Analysis of primary productivity and phytoplankton abundance across coastal ecosystems: Implications for sustainable aquaculture and ecosystem management - Dongoran, Khoirul Zaman; Nyompa, Achmad Husein (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The coastal waters of Maros, encompassing ponds, estuaries, and open seas, exhibit diverse environmental conditions influencing primary productivity and phytoplankton abundance. Understanding these variations is crucial for sustainable management of coastal ecosystems and the optimization of aquaculture activities. This study analyzed primary productivity and phytoplankton abundance across three distinct Methods: ecosystems: ponds, estuaries, and seas in the coastal waters of Maros. Sampling was conducted using a stratified approach, measuring key environmental parameters such as nutrient concentrations, salinity, and temperature. Phytoplankton abundance was quantified using microscopy, while primary productivity was assessed through light-dark bottle techniques. Results: The findings revealed significant differences in primary productivity and phytoplankton abundance among the ecosystems. Ponds exhibited the highest primary productivity due to elevated nutrient input from anthropogenic activities, while estuaries displayed moderate productivity influenced by fluctuating salinity and nutrient mixing. The sea, despite having lower productivity, showed higher phytoplankton diversity due to stable environmental conditions. Each ecosystem was dominated by distinct phytoplankton species adapted to their specific environmental characteristics. Conclusion: This study highlights the substantial impact of environmental factors on primary productivity and phytoplankton distribution in the coastal waters of Maros. The findings provide insights into the ecological dynamics of these ecosystems, emphasizing the importance of tailored management strategies to balance aquaculture practices and ecosystem sustainability. Novelty/Originality of this article: This research provides a comprehensive comparative analysis of primary productivity and phytoplankton abundance across three interconnected ecosystems in Maros, offering novel insights into their ecological interactions and implications for sustainable aquaculture and coastal management.